Step
*
1
of Lemma
rnexp-convex
1. a : ℝ
2. b : ℝ
3. r0 ≤ b
4. b ≤ a
5. n : ℤ
6. 0 < n
7. a - b^n ≤ (a^n - b^n)
⊢ ((a^n - b^n) * (a - b)) ≤ ((a^n * a) - b^n * b)
BY
{ (nRNorm 0 THEN Auto) }
1
1. a : ℝ
2. b : ℝ
3. r0 ≤ b
4. b ≤ a
5. n : ℤ
6. 0 < n
7. a - b^n ≤ (a^n - b^n)
⊢ ((a^n * a) + -(a^n * b) + -(b^n * a) + (b^n * b)) ≤ ((a^n * a) + -(b^n * b))
Latex:
Latex:
1.  a  :  \mBbbR{}
2.  b  :  \mBbbR{}
3.  r0  \mleq{}  b
4.  b  \mleq{}  a
5.  n  :  \mBbbZ{}
6.  0  <  n
7.  a  -  b\^{}n  \mleq{}  (a\^{}n  -  b\^{}n)
\mvdash{}  ((a\^{}n  -  b\^{}n)  *  (a  -  b))  \mleq{}  ((a\^{}n  *  a)  -  b\^{}n  *  b)
By
Latex:
(nRNorm  0  THEN  Auto)
Home
Index